Economic cooperation in higher education between China and Europe - Kazakova, Nadiia; Neustroieva, Gelena; Hromov, Vadym (Національний технічний університет "Харківський політехнічний інститут", 2023)
The article deals with the scientifically substantiated analyses of the problem of economic cooperation in the field of higher education between China and Europe based on its essential importance for the world problem of developing new innovative sides of higher education. Taking into account the scientific and innovative development of China it is necessary to conduct analyses of the problems of educational-research cooperation between universities of China and EU. This article examines the following analytical questions and identifies factors affecting the development of the education system in modern economic conditions. Factor analysis makes it possible to form the concept of development of economic cooperation in the established macro- and microeconomic conditions; predict educational potential using quantitative assessments and taking into account structural changes and the number of students; to combine supply and demand for highly qualified specialists in popular specialties for the innovative economy. To do this, using a factor approach, it is necessary to monitor the state of scientific and educational cooperation between Chinese and European universities according to key indicators. The general provisions on analysis for solving this problem are given and it is estimated that the analytical approach is the most acceptable, since it allows you to build a diagram for comparing percentage of the quantity of Chinese students in European universities and the quantity of European students at Chinese universities. It is advisable to consider the process of developing and financing the exchange programs for students as the most important factor for educational cooperation. This research paper reveals the fact that China owes its economic growth mainly to the intensive development of its innovations and investments into the education cooperating with foreign countries, using own human resources and raw materials. The article analyzes economists’ views on the process of solving the educational problems of cooperation in the field of education. It should be noted that various educational and scientific programs and initiatives have been established within the framework of cooperation between China and Europe in the field of higher education. One of the key benefits of collaboration is that each party can access the best practices and technologies used by the other party. In order to create an innovative economy, it is necessary to create a human resourse reserve for high-tech and knowledge-intensive industries of the future. Therefore, the task of universities is to provide education at the level of world standards. The research has been developed to estimate that China is a leading country in the educational sector of the economy, which include improving public funding through the creation of a system of subsidies and educational loans, attracting social partnership resources, and using distance learning. The EU and China have agreed to promote the study and teaching of Chinese and European languages, which will allow expanding contacts between people, reaffirming their commitment to multilingualism. The process of cooperation between China and European countries in the sphere of high education, which is currently unfolding, aims to facilitate the development of industrial 4.0 and technology hub in China.

Cтаття присвячена науково обґрунтованому аналізу проблеми економічного співробітництва у сфері вищої освіти між Китаєм та Європою з огляду на її істотне значення для світової проблеми розвитку нових інноваційних аспектів вищої освіти. Враховуючи науково-інноваційний розвиток Китаю, необхідно провести аналіз проблем освітньо-дослідницького співробітництва між університетами Китаю та ЄС. У статті розглянуто такі аналітичні питання та визначено чинники, що впливають на розвиток системи освіти в сучасних економічних умовах. Факторний аналіз дає можливість сформувати концепцію розвитку економічного співробітництва в сформованих макро- та мікроекономічних умовах; прогнозувати навчальний потенціал за допомогою кількісних оцінок та з урахуванням структурних змін і кількості учнів; поєднати попит і пропозицію на висококваліфікованих спеціалістів затребуваних спеціальностей для інноваційної економіки. Для цього за допомогою факторного підходу необхідно провести моніторинг стану науково-освітньої співпраці університетів Китая та Европи за ключовими показниками. Наведено загальні положення щодо аналізу для вирішення цієї проблеми та оцінено, що аналітичний підхід є найбільш прийнятним, оскільки дозволяє побудувати діаграму для порівняння відсотка кількості китайських студентів у європейських університетах та кількості європейських студентів в китайських університетах. Доцільно розглядати процес розробки та фінансування програм обміну для студентів як найважливіший фактор освітньої співпраці. Ця дослідницька стаття показує той факт, що Китай своїм економічним зростанням завдячує головним чином інтенсивному розвитку своїх інновацій та інвестиціям в освіту і співпрацює з іноземними країнами, використовуючи власні людські ресурси та сировину. У статті аналізуються погляди економістів на процес вирішення освітніх проблем співробітництва в освітній сфері. Слід зазначити, що в рамках співпраці між Китаєм і Європою у сфері вищої освіти започатковано різноманітні освітні та наукові програми та ініціативи. Однією з ключових переваг співпраці є те, що кожна сторона може отримати доступ до найкращих практик і технологій, які використовує інша сторона. Для створення інноваційної економіки необхідно створити кадровий резерв для високотехнологічних і наукомістких галузей майбутнього. Тому завдання університетів – дати освіту на рівні світових стандартів. Дослідження було розроблено для оцінки того, що Китай є провідною країною в освітньому секторі економіки, що включає покращення державного фінансування через створення системи субсидій та освітніх кредитів, залучення ресурсів соціального партнерства та використання дистанційного навчання. ЄС і Китай домовилися сприяти вивченню та викладанню китайської та європейських мов, що дозволить розширити контакти між людьми, таким чином країни підтвердили свою відданість багатомовності. Процес співпраці між Китаєм та європейськими країнами у сфері вищої освіти, який зараз розгортається, спрямований на сприяння розвитку індустріального 4. 0 та технологічного хабу в Китаї.
Економічне співробітництво у сфері вищої освіти між Китаєм та Європою
Keywords: higher education; educational problems; framework of the cooperation program; scientific research; вища освіта; освітні проблеми; рамки програми співпраці; наукові дослідження